Determinan Suku Bunga dan Likuiditas Bank Terhadap Pertumbuhan Kredit di Indonesia - Yeniwati Yeniwati (Jurnal Ecogen, 2020)
This study aims to determine the effect of the interest rate (BI rate) on bank credit growth in Indonesia, liquidity on bank credit growth in Indonesia and determine the effect of interest rates and liquidity on bank credit growth in Indonesia. The method used in this study is Ordinary Least Square (OLS) using secondary data from 2009 Quarter I to 2018 Quarter IV. The results of the analysis showed that there was an influence between interest rates on bank credit growth in Indonesia, there was an influence between liquidity on bank credit growth in Indonesia. Together there is an influence between interest rates and bank liquidity on the growth of bank credit in Indonesia. The policy implication of this research is that Bank Indonesia must maintain the benchmark interest rate set in order to trigger an increase in bank credit growth. In addition, Bank Indonesia must monitor the liquidity of commercial banks in Indonesia so that the trust of the banking community is even greaterKeywords : interest rate, Liquidity, Credit